2017
DOI: 10.1002/jmri.25885
|View full text |Cite
|
Sign up to set email alerts
|

Native T1 reference values for nonischemic cardiomyopathies and populations with increased cardiovascular risk: A systematic review and meta‐analysis

Abstract: BackgroundAlthough cardiac MR and T1 mapping are increasingly used to diagnose diffuse fibrosis based cardiac diseases, studies reporting T1 values in healthy and diseased myocardium, particular in nonischemic cardiomyopathies (NICM) and populations with increased cardiovascular risk, seem contradictory.PurposeTo determine the range of native myocardial T1 value ranges in patients with NICM and populations with increased cardiovascular risk.Study TypeSystemic review and meta‐analysis.PopulationPatients with NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 86 publications
(267 reference statements)
2
20
0
Order By: Relevance
“…Based on these limited available studies no conclusion can be drawn on the clinical relevance of T 2 and T 2 * mapping. More research could enable to determine the clinical applicability of these mapping techniques, while T 1 mapping has already shown to be promising in distinguishing hypertension related LVH and HCM [21,206]. Furthermore, as the incidence of cardiomyopathies is related to obesity and T2DM [8] it is important to determine whether these high cardiovascular risk factors cause myocardial tissue adaptation and if these are distinguishable with quantitative techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these limited available studies no conclusion can be drawn on the clinical relevance of T 2 and T 2 * mapping. More research could enable to determine the clinical applicability of these mapping techniques, while T 1 mapping has already shown to be promising in distinguishing hypertension related LVH and HCM [21,206]. Furthermore, as the incidence of cardiomyopathies is related to obesity and T2DM [8] it is important to determine whether these high cardiovascular risk factors cause myocardial tissue adaptation and if these are distinguishable with quantitative techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, the European Society of Cardiology recently described a shifting standards from the assessment of LGE towards the use of T 1 and T 2 mapping in their latest position statement [20]. The clinical utility of T 1 mapping has already been acknowledged and included in some guidelines [8,13,21,22]. In addition, other guidelines also advocate to include T 2 and T 2 * mapping instead of T 2 -weighted imaging [20,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, native T1 mapping detects abnormalities of both the extracellular matrix and the myocytes, while partition coefficient and synthetic extracellular volume are more specific for extracellular matrix expansion. 22 We hypothesise that the increased native T1 times are primarily reflecting underlying structural abnormalities in the myocytes, not the extracellular matrix. Indeed, a study by Swaboda et al used multivariable modelling in adult hypertrophic cardiomyopathy patients to demonstrate a correlation between native T1 and myocardial mechanics but not extracellular volume fraction, suggesting that the structural abnormalities resulting in impaired function were cellular.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, a study by Swaboda et al used multivariable modelling in adult hypertrophic cardiomyopathy patients to demonstrate a correlation between native T1 and myocardial mechanics but not extracellular volume fraction, suggesting that the structural abnormalities resulting in impaired function were cellular. 22 Previous studies in adult hypertrophic cardiomyopathy have demonstrated a statistically significant difference in native T1 between hypertrophic cardiomyopathy and controls. 23 Indeed, some reports have suggested that native T1 can be used to distinguish between patients with and without hypertrophic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 96%
“…The native T1 strong correlates with histological myocardial fibrosis in patients with aortic stenosis [21]. In 2018, a meta-analysis established the reference values of native T1 for nonischemic cardiomyopathies and populations with increased cardiovascular risk [22]. Different types of tissue will have their own normal ranges of values, and a significant departure from the normal range is thought to differentiate between normal and abnormal myocardium.…”
Section: Introductionmentioning
confidence: 99%